Kang Dedi Mulyadi Populist Communication and Its Impact on Local Leadership Perception - Dilian, Marlita; Oktavia, Lisvia Dianty; Fariskha, Tiffany Shafa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study investigates how Kang Dedi Mulyadi (KDM) populist communication style influences public perceptions of local leadership in West Java. Through qualitative literature review, the research synthesizes insights from scholarly works, media analyses, and contextual sources to explore symbolic, cultural, and emotional dimensions of KDM leadership communication. Findings reveal that his use of Sundanese cultural codes, informal language, and direct grassroots engagement constructs an image of authenticity, empathy, and accessibility—enhancing short-term legitimacy while fostering strong emotional connections with constituents. Digital platforms amplify his persona by transforming political communication into viral, emotionally resonant storytelling that bridges the gap between elite governance and everyday citizens. Nevertheless, the research identifies critical concerns regarding sustainability of leadership models built primarily on symbolic action and performative gestures. While KDM communication resonates strongly with grassroots communities and redefines leadership legitimacy, it risks overshadowing institutional reform, policy depth, and governance sustainability. Such duality reveals the ambivalent nature of populist-local leadership in Indonesia: effective in mobilizing trust and visibility, yet vulnerable when not embedded within structural accountability and participatory governance frameworks